2010
DOI: 10.1103/physrevb.81.045324
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dissociative fragment-adsorbate interaction energy during chemisorption of the diatomic molecule HCl on Si(100)

Abstract: This study investigates the surface chemistry and the ordering characteristics of coadsorbed hydrogen and chlorine atoms, generated by the exposure of the Si͑100͒ surface to gas-phase HCl molecules at various substrate temperatures, by scanning tunneling microscopy ͑STM͒, core-level photoemission spectroscopy, and Monte Carlo simulation. Experimental results show that saturation exposure to HCl causes all surface dangling bonds to be terminated by the two fragments H and Cl atoms and that the number of H-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Earlier experiments of HCl and HBr on Si(100) were performedin contrast to the present workat saturation coverage or on a hydrogenated surface . While dissociative attachment was found to be a major pathway, previous authors found evidence of the abstraction of single atoms, H or Cl, by the surface.…”
Section: Introductioncontrasting
confidence: 56%
“…Earlier experiments of HCl and HBr on Si(100) were performedin contrast to the present workat saturation coverage or on a hydrogenated surface . While dissociative attachment was found to be a major pathway, previous authors found evidence of the abstraction of single atoms, H or Cl, by the surface.…”
Section: Introductioncontrasting
confidence: 56%
“…While there are other gaseous constituents in the chamber during dosing that could contribute to these features, those are predominantly Ar and H 2 (low sticking coefficient) as well as HCl, which does not appear to be present in significant amounts on our dosed surfaces. HCl appears in STM as small, alternating round features that we have observed when the Ar is removed from the AlCl 3 bottle before dosing (see Figure S2 in the Supporting Information). However, as stated before, Ar was left in the bottle for these experiments, mitigating HCl generation.…”
Section: Resultsmentioning
confidence: 83%
“…The etching of Cl atoms have been previously studied and reported by many groups. [29][30][31][32][33] But, Eq. 11 represents Cl etch during the epitaxy growth, which differs remarkably from a simple Si vapor etching.…”
Section: Resultsmentioning
confidence: 99%